Ratcheting and low cycle fatigue of nickel-based alloy GH3536 formed by selective laser melting at 800 °C. (4th July 2022) - Pan, Lingfeng; Ding, Peishan; Yan, Kun; Ma, Linwei; Zheng, Xiaotao
ABSTRACT: The cyclic uniaxial stress-controlled ratcheting behaviour of GH3536 formed by selective laser melting (SLM) was tested at 800 °C. The effects of different stress rates and building orientations of 0°, 45° and 90° were investigated. Results present that the ratcheting behaviour of SLM GH3536 at 800 °C exhibits significant stress rate dependence. Moreover, the accumulated ratcheting strain increasing with increasing the stress amplitude and stress rate. It is noted that the building orientation angle of the specimen has an important influence on the mechanical performance. The 45° specimen in the experimental conditions has the greatest low cycle fatigue life. The ratcheting evolution over the whole cyclic load history can be divided into three stages. The relationship between steady ratcheting strain range and low cycle fatigue life was established.